PUSAT INFORMASI BENCANA MERAPI: KOMPETISI JURNALISME PEMERINTAH, MEDIA DAN WARGA DI TWITTER - Harnita, Pratiwi Cristin; Krisnawati, Ester; Abraham, Rendy Hermanto (Master of Communication Science Program, Universitas Diponegoro, 2024)
This study aims to analyze the pattern of disaster communication related to the eruption of Mount Merapi through social media Twitter with the Social Network Analysis (SNA) approach. The data was obtained using tweet-harvest and analyzed using the Gephi 0.10 application with a focus on the main hashtags: #awan_panas_merapi, #gempa_vulkanik_merapi, #erupsi_gunung_merapi, #bencana_merapi, and #SiagaMerapi. The results of the study show that disaster communication on Twitter forms three main patterns: vertical, horizontal, and interactive. The government, through accounts such as @BPPTKG, acts as the main source of information that disseminates official data. Mass media serves as a bridge of information to a wider audience, while community accounts such as @merapi_uncover become significant actors in conveying real-time and visual information that is close to the community